The effect of the legislative context on the significance of the Quranic analogy A study in light of Shiite interpretations - Jahina Abdul-Kadhim Saad Abboud; Prof. Majeed Tarish Abid (PH Dr.) (Journal of College of Education, 2025)
Context indicates connection, sequence, succession, and consistency. That is: the succession of words contained in one context in meaning; A word should not be interpreted with a meaning that contradicts its structure. Context has an important function in understanding Quranic texts, investigating the purposes of Quranic words and structures, and clarifying their meanings. Context is what reveals the ambiguity of meaning and directs it.The term “Sharia” is applied to all the doctrinal and jurisprudential issues and rulings that regulate the lives of people, and this division was one of the requirements of the classification, as the curriculum consists of all these issues and they constitute the law of God.The analogy was mentioned in the Holy Qur’an in the legislative context, and the legislative context was the revealer of this analogy and explained it. We found this revelation among the Shiite interpreters of the Holy Qur’an in a large number of Qur’anic verses that were mentioned in the legislative context in the Holy Qur’an.
Keywords: Context, Legislation, Analogy